Transformation of the Tanzania medical store department through global fund support: an impact assessment study. Issue 11 (6th November 2020) - Githendu, Patrick; Morrison, Linden; Silaa, Rosemary; Pothapregada, Sai; Asiimwe, Sarah; Idris, Rafiu; Peterson, Tatjana; Davidson, Emma; Lesego, Abaleng; Mwale, Neema; Mwakalobo, Sako Mayrick; Bwanakunu, Laurean Rugambwa; et al.
Abstract : Background: The Tanzania government sought support from The Global Fund to Fight AIDs, Tuberculosis and Malaria to reform its Medical Stores Department, with the aim of improving performance. The study sought to assess the impact of the reforms and document the lessons learnt. Methods: Quantitative and qualitative research methods were applied to assess the impact of the reforms. The quantitative part entailed a review of operational and financial data covering the period before and after the implementation of the reforms. Interrupted time series analysis was used to determine the change in average availability of essential health commodities at health zones. Qualitative data were collected through 41 key informant interviews. Participants were identified through stakeholder mapping, purposive and snowballing sampling techniques and responses were analysed through thematic content analysis. Results: Availability of essential health commodities increased significantly by 12.6% (95% CI 9.6% to 15.6%) after the reforms and continued to increase on a monthly basis by 0.2% (95%CI 0.0% to 0.3%) relative to the preintervention trend. Sales increased by 56.6% while the cost of goods sold increased by 88.6% between 2014/2015 and 2017/2018. Surplus income increased by 56.4% between 2014/2015 and 2017/2018 with reductions in rent and fuel expenditure. There was consensus among study participants that the reforms were instrumental in improving performance of the Medical Stores Department. Conclusion: Positive results were realised through the reforms. However, despite the progress, there were risks such as the increasing government receivable that could jeopardise the sustainability of the gains. Therefore, multistakeholder efforts are necessary to make progress and expand public health.